Urban growth: Modelling street network growth in Manhattan (1642–2008) and Barcelona (1260–2008) - Al Sayed, Kinda; Hanna, Sean; Penn, Alan (Frontiers in Built Environment, 2022)
In this paper, we argue for the case that cities are self-organised complex systems by presenting evidence on positive and reinforcing feedback mechanisms and robust global trends that characterise historical growth patterns. In two case studies; Manhattan and Barcelona, historical stages of urban growth were mapped and analysed. The analyses revealed regularities that may help define the local and global processes that characterise urban growth marked by alternating periods of expansion and pruning in street networks. The global trend marked by a lognormal distribution of segmental integration (closeness) in street networks was consistently restored following planning interventions. The overall street network growth trend appeared to fit an exponential or power law distribution, along with a linear change in fractal dimension. Underlying these global trends, we found evidence for local positive and reinforcing feedback mechanisms; explained by preferential attachment of new streets to well-connected street structures, and pruning of weakly integrated local street structures. The findings are likely to improve our understanding of urban growth.